Sexual Violence in and around the Classroom. (January 2017) - Graybill, Rhiannon; Minister, Meredith; Lawrence, Beatrice
Abstract: Sexual violence on campus is a major issue facing students, faculty, and administrators, and institutions of higher education are struggling to respond. This forum brings together three responses to the problem, with a focus on the religious studies classroom. The responses move from the institution to the faculty to the classroom, exploring three separate but linked spaces for responding to sexual violence. The first contribution (Graybill) critiques common institutional responses to sexual violence. The second contribution (Minister) advocates for long‐term, classroom‐based responses to sexual violence and describes a faculty/staff workshop response. The third contribution (Lawrence) emphasizes the classroom, examining the issues that arise when perpetrators of sexual assault are part of the student body. Read together, the pieces offer a comprehensive view of the complicated intersections of sexual violence, the university, and pedagogical issues in religious studies.